2014
DOI: 10.1371/journal.pone.0096622
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Repeated Low Dose against Single High Dose of Kainate in C57BL/6J Mouse Model of Status Epilepticus: Behavioral and Electroencephalographic Studies

Abstract: A refined kainate (KA) C57BL/6J mouse model of status epilepticus (SE) using a repeated low dose (RLD) of KA (5 mg/kg, intraperitoneal; at 30 min intervals) was compared with the established single high dose (SHD) of KA (20 mg/kg, intraperitoneal) model. In the RLD group, increased duration of convulsive motor seizures (CMS, Racine scale stage ≥3) with a significant reduction in mortality from 21% to 6% and decreased variability in seizure severity between animals/batches were observed when compared to the SHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(165 citation statements)
references
References 62 publications
9
148
3
Order By: Relevance
“…Our findings confirm a previous report (Tse et al, 2014) that low-dose, repeated KA administration serves as a useful paradigm for high rates of SE induction with limited mortality in C57BL/6J mice. Unique to our study, we demonstrate cell death can be readily observed in the hippocampus and limbic structures following repeated, low-dose KA administration in C57 mice.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings confirm a previous report (Tse et al, 2014) that low-dose, repeated KA administration serves as a useful paradigm for high rates of SE induction with limited mortality in C57BL/6J mice. Unique to our study, we demonstrate cell death can be readily observed in the hippocampus and limbic structures following repeated, low-dose KA administration in C57 mice.…”
Section: Discussionsupporting
confidence: 92%
“…We observe that systemic, low-dose KA administration (i.p.) reliably produces SE without acute mortality (7d), similar to reports by Tse et al (2014). Additionally, low-dose KA insults result in features indicative of TLE pathology, including hippocampal neurodegeneration and astrogliosis.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations